Antioxidant and cytoprotective activities of marine fungi isolated from brown seaweeds in Nha Trang Bay, Khanh Hoa Province, Central Vietnam - Ngo , Thi Duy Ngoc; Phan, Thi Hoai Trinh; Yurchenko, Ekaterina A.; Yurchenko, Anton N.; Cao, Thi Thuy Hang; Vo , Thi Dieu Trang; Tran, Thi Thanh Van; Pham, Duc Thinh; Huynh Hoang, Nhu Khanh; Bui, Thi Nam Phuong (Vietnam Journal of Marine Science and Technology, 2024)
This study aims to evaluate the antioxidant and cytoprotective activities of 32 fungal strains isolated from brown seaweeds collected from Nha Trang Bay, Khanh Hoa Province, Central Vietnam. These fungal extracts were screened for antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radical scavenging assay. In contrast, cytoprotective activity on rat cardiomyocytes H9c2 cell line was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) assay. The results indicated the capacity for free DPPH and ABTS radical scavenging of fungal crude extracts with 31.25% (n = 10) and 81.25% (n = 26), respectively. Among the fungal strains with high antioxidant activity, the three fungal extracts 2104NT-1.3, 2104NT-3.3, and 2104NT-7.7 increased the viability of rotenone-exposed cardiomyocyte cells by 9.9%, 15.2%, and 13.6%, respectively. Three fungal strains with significant antioxidant and cytoprotective activities were identified as Penicillium chermesinum 2104NT-1.3, Aspergillus sp. 2104NT-3.3, and Penicillium sp. 2104NT-7.7 based on sequence analysis of internal transcribed spacer (ITS) region. This study provided the potential fungal strains isolated from Nha Trang Bay for further investigation of antioxidant and cytoprotective compounds.